Impact of pressure and temperature on tetra-n-butyl ammonium bromide semi-clathrate process for carbon dioxide capture - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (International Conference on Applied Energy, ICAE2014, 2014)
The pre-combustion capture of CO2 in an IGCC power plant employing the hydrate based gas separation (HBGS) process is a novel method currently receiving attention around the world. Tetra-n-butyl ammonium bromide (TBAB) is a promoter that has been shown to improve the efficiency of hydrate formation. In this study, the effect of temperature and pressure on 0.3 mol% TBAB solution is investigated. The induction time for the experiments conducted at 6.0 MPa and 274.8 K was found to be lower, while nucleation became increasingly random as temperature is increased and pressure is reduced. Total gas uptake and normalized rate of hydrate formation (NR5) is also the highest for the experiments conducted at 6.0 MPa and 274.8 K. However, it was found that the hydrate phase CO2 composition remains relatively constant at both reduced temperatures and pressures. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; Promoters; tetra-n-butyl ammonium bromide